2012
DOI: 10.1002/bit.24471
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte counting from a small amount of whole blood using a size‐controlled microcavity array

Abstract: Absolute counting of total leukocytes or specific subsets within small amounts of whole blood is difficult due to a lack of techniques that enable separation of all leukocytes from limited amounts of whole blood. In this study, a microfluidic device equipped with a size-controlled microcavity array for highly efficient separation of leukocytes from submicroliters of whole blood was developed. The microcavity array can separate leukocytes from whole blood based on differences in the size and deformability betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The device was microfabricated as described (Hosokawa et al, 2009(Hosokawa et al, , 2012. In brief, a poly(ethylene terephthalate) plate (20 3 20 mm, thickness = 38 µm) was used as the substrate.…”
Section: Single-cell Analysismentioning
confidence: 99%
“…The device was microfabricated as described (Hosokawa et al, 2009(Hosokawa et al, , 2012. In brief, a poly(ethylene terephthalate) plate (20 3 20 mm, thickness = 38 µm) was used as the substrate.…”
Section: Single-cell Analysismentioning
confidence: 99%
“…Since RBCs can deform through openings (1–2 µm) much smaller than their diameter (~8 µm), while circulating leukocytes are spherical with diameters 6–8 μm 22 , microfilters consisting of pillars 23, 24 , weirs 23, 25, 26 , and membrane pores 23, 27 have been developed to separate these leukocytes from RBCs. A key limitation in directly processing whole blood using microfiltration is the potential for cells to clog and foul the filter microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Diluted blood samples (200 μL containing 1 μL of whole blood) were applied to the microcavity array at the flow rate of 200 μL/min. Under these conditions, 97.17 4.7% of leukocytes were recovered on the surface of the microcavity array (Hosokawa et al, 2012). Light with a wavelength of 464.5-499.5 nm was used for cell imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has demonstrated a novel microfluidic device equipped with a size-controlled microcavity array for CD4 testing (Hosokawa et al, 2012(Hosokawa et al, , 2013. The microcavity array can separate leukocytes from a few microliters of whole blood as small as those obtained by a finger prick based on differences in the size of leukocytes and other blood cells.…”
Section: Introductionmentioning
confidence: 99%